Serotypes of beta-hemolytic Treponema hyodysenteriae. - Baum, D H (1979)
Cultures form 13 isolates of pathogenic, beta-hemolytic Treponema hyodysenteriae from 11 geographically separate outbreaks and 2 experimentally induced cases of swine dysentery were lyophilized and extracted with hot phenol-water. The resulting water phases were examined serologically with antisera produced in rabbits against whole-cell bacterins of the 13 isolates for evidence of antigenic classes within the species. Water-phase antigens gave precipitin reactions with homologous antisera. Results from cross-testing of each water phase with each antiserum showed four serologically distinct groups among the isolants examined. Based on precipitin reactions in agarose gel, four serotypes of pathogenic, beta-hemolytic T. hyodysenteriae are proposed.